Study of Neural Cell Growth on Different Microelectrode Surfaces - 张华 朱壮晖 吴蕾 陈强 金庆辉 李刚 赵建龙 (东华大学学报（英文版）, 2012)
The paper is aimed to investigate the adhesion and growth of neural cells on different microelectrode surfaces and their possible mechanism, thereby an optimum interfacial material or substrate for neural microelectrode can be chosen. Three different materials including platinum, gold, and pyrolyzed photoresist derived carbon material, in the forms of plasma.treated and non-treated ones, were tested. Surface properties of the microelectrodes in terms of surface morphology and wettability were examined; then their biocompatibility was tested by co-culturing with SK-N-SH ncuroblastoma cells. Results of experiments demonstrated that, compared with platinum and gold, carbon could be a better substrate for cell adhesion and growth, especially for the plasma- treated carbon surface. The high wetting property of plasma-treated carbon accounted for the preferable adhesion of cell on its surface. Therefore, plasma-treated carbon can potentially be employed for fabrication of biocompatible and stable neural electrodes, which is beneficial for neural engineering research, such as regeneration from injury or disease therapy of neural system.